A hybrid, iterative approach, to support the development of fit-for-purpose sensor-derived measures - Ballester, Belen R.; Reaney, Matthew; Mack, Christina; Ajraoui, Salma (Frontiers in Medical Technology, 2025)
Digital Health Technologies (DHTs) hold immense potential for transforming drug development. Although innovation in the DHT space has been rapid, the approval process for these technologies remains slow due to fragmented efforts from industry and researchers, as well as regulatory challenges. In this position paper, we propose a hybrid methodology and approach for developing fit-for-purpose DHTs for assessment by integrating both patient-centric and data-centric elements. By emphasizing patient relevance while considering device and data feasibility, we can advance the development of patient-centric digital measures efficiently without compromising measurement precision. Ultimately, this hybrid approach aims to streamline the approval process, foster collaboration among stakeholders, and accelerate the integration of DHTs into clinical practice, thereby enhancing the overall efficiency and effectiveness of drug development.